2021
DOI: 10.1101/2021.07.01.21259404
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Epidemiological dynamics of SARS-CoV-2 VOC Gamma in Rio de Janeiro, Brazil

Abstract: The emergence and widespread circulation of SARS-CoV-2 variants of concern (VOC) or interest (VOI) imposes an enhanced threat to global public health. In Brazil, one of the countries most severely impacted throughout the pandemic, a complex dynamics involving variants co-circulation and turnover events has been recorded with the emergence and spread of VOC Gamma in Manaus in late 2020. In this context, we present a genomic epidemiology investigation based on samples collected between December 2020 and May 2021… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
(71 reference statements)
0
1
0
Order By: Relevance
“…This small number allows the virus to circulate freely within the population, enabling the emergence of mutations and further diversification into new lineages. Previous studies analyzing the spatial progression of the pandemic in Brazil revealed that the states of São Paulo and Rio de Janeiro were pivotal to the dissemination of lineages throughout the country, including VoCs [8][9][10][11]. Rio de Janeiro was also the background to the emergence and worldwide spread of the Variants of Interest (VoI) Zeta (P.2) [12].…”
Section: Introductionmentioning
confidence: 99%
“…This small number allows the virus to circulate freely within the population, enabling the emergence of mutations and further diversification into new lineages. Previous studies analyzing the spatial progression of the pandemic in Brazil revealed that the states of São Paulo and Rio de Janeiro were pivotal to the dissemination of lineages throughout the country, including VoCs [8][9][10][11]. Rio de Janeiro was also the background to the emergence and worldwide spread of the Variants of Interest (VoI) Zeta (P.2) [12].…”
Section: Introductionmentioning
confidence: 99%